Making a Web-Portal With Aquaculture Sustainability Indicators for the General Public - Mikkelsen, Eirik; Myhre, Magnus Stoud; Robertsen, Roy; Winther, Ulf (Frontiers in Sustainable Food Systems, 2021)
The sustainability of aquaculture is a complex issue that can be hard to assess and communicate. Communicating it to the general public is in many ways an even bigger challenge than communicating to experts on sustainability or aquaculture. The general public's perception of the status and challenges for sustainability is important for the development of the aquaculture industry and for society at large, through its roles both as consumers and electorate, and generally in providing or denying a “social license to operate” for the industry. This paper presents the process and challenges involved in choosing and quality assuring sustainability indicators for Norwegian aquaculture, covering environmental, economic, and social dimensions. It involved a team of researchers, a quality assurance group, IT developers and designers, a literature review, a national survey, and user-testing, all to establish criteria for selecting data and indicators and how to present them, and to do the actual production. The endpoint is a web-portal with indicators currently covering 22 themes, aimed at anyone interested in the sustainability of Norwegian fish farming. The portal does not conclude if or to what degree Norwegian fish farming is sustainable, as that would require making valuation and trade-offs among different sustainability objectives. Many indicators are automatically updated, and data are only from publicly available sources and produced by the authorities or research institutions. The portal is under continuous development, with new themes and indicators, and improving spatial and temporal resolution.